Depresi pada Mahasiswa Teologi & Terapi Experiential REBT & Psychodynamic Kristen: Sebuah Studi Kasus Kolektif - Daniel Trihandarkha (SIAP: Jurnal Teologi dan Pendidikan Kristen, 2022)
Depression syndrome in theological students has been scarcely examined. The students who come from various places and cultural background often arrive in the school with unresolved problems internally, thus affecting the academic achievement and impairing the social functioning skills. The case study purposively sampling four students with presented depressive symptom who expressed emotional distress, physical discomfort and several suicidal ideations. The students themselves were and are the author’s students in 12 years’ experience in teaching formal and non-formal Christian course or Theological studies. During the three months encounters and short sessions in class and out class, several students were able to have decent therapeutic alliance, and fulfil the agreed goals together.  Conclusively, students who were able to share and express their struggles in helpful and supportive environment could thrive positively and showed visible change in behaviour, symptoms and achievement. The spiritual discipline of meditating the Scripture and praying about it played a significant role in, and the usage of REBT and Psychodynamic are beneficial in exploring the repressed emotions and the subscribed irrational beliefs.Keywords: Students, distress, REBT, psychodynamic, Christians,